PENINGKATAN HAK GUNA BANGUNAN RUMAH TINGGAL DIBEBANI HAK TANGGUNGAN MENJADI HAK MILIK DIATAS HAK PENGELOLAAN - Aflinda Dewi (STIH Putri Maharaja, 2019)
The time period given to Building Utilization Rights for houses and used as collateral for debts by the Debtor, will cause legal problems in the future, the debtor does not have legal certainty regarding his rights, and for Creditors it will be difficult to sell in the event of bad credit. Debtor based on PerMenAg / Ka. The Land Agency Number 5 of 1998, can apply for an increase in ownership rights without paying off the debt first. Requests for increased rights can be processed after the Debtor has received written approval from the Creditors. For the continuity of credit guarantee prior to HM Upgrade, SKMHT is made. This article is based on the implementation of the Increased Right to Use for Residential Buildings which are burdened with Underwriting rights to Ownership Rights at the Land Office of Padang City by using the Empirical Juridical Method, where the author conducts research directly into the Padang City land office. Conclusion of the implementation of increasing use rights of residential buildings which are burdened with mortgage rights at the Land Office based on the Minister of Religion / Head of BPB No. 5 of 1998, carried out according to the procedure, does not take a long time and costs a lot.